Pengaruh Efikasi Diri dan Motivasi Berprestasi terhadap Kecemasan Menghadapi Pertandingan Sepak Bola pada Pemain Bola SSB Bintang Ragunan - Selviana Selviana; Krisna Dwi (Universitas Persada Indonesia YAI, 2022)
Football is a sport that is popular with Indonesians from children to adults. For individuals who specifically attendsoccer school, facing each match can cause anxiety in itself because of the hope of winning. This study aims todetermine the relationship between efikasi diri and achievement motivation with anxiety facing football match onplayers SSB Bintang Ragunan. The sampling technique used a census (saturated sample) totaling 90 people. The datacollection method uses a Likert scale. Test instrument in this study using three scales, the scale of the Match FacingAnxiety consisted of 32 items and 25 items are valid, efikasi diri Scale consists of 24 items and 21 items are valid,Achievement Motivation scale consists of 36 items and 25 items are valid. Based on the results of data analysis usingSPSS, the correlation coefficient (r) =0.428 and p = 0.000 <0.05, The conclusion of this research that there issignificant relationship with the positive direction between self-efficacy and achievement motivation and anxietyfacing football match on players SSB Bintang Ragunan